Determinants of ventilatory inefficiency in transthyretin cardiac amyloidosis: The role of excessive ventilatory drive - Monfort, Astrid; Thevenet, Eugenie; Lacavalerie, Mickael Rejaudry; Banydeen, Rishika; Inamo, Jocelyn; Neviere, Remi (Frontiers in Physiology, 2022)
Background and objective Along with impaired aerobic capacity, increased slope of the relationship between ventilation (VE) and pulmonary CO2 output (VCO2), i.e., VE-VCO2 slope is a common finding in patients with cardiac amyloidosis (CA), which suggests ventilatory inefficiency. Little is known about mechanisms leading to ventilatory inefficiency in CA patients. We tested whether ventilatory inefficiency in transthyretin hereditary CA patients would be associated with excessive ventilatory drive, inability of pulmonary blood flow to increase adequately during exercise and excessive sympathetic stimulation, which are known mechanisms of VE-VCO2 slope increase. Methods In this single-center retrospective observational study, consecutive patients (n=41) with known familial transthyretin amyloidosis p.Val142Ile mutation carriers with confirmed cardiac phenotype were included. Results Compared with CA patients without ventilatory inefficiency (VE-VCO2 slope<36), patients with ventilatory inefficiency (VE-VCO2 slope≥36) had increased inter-ventricular septum thickness, lower VO2 peak along with hyperventilation, and prolonged post-exercise heart rate recovery. By multivariate analysis, only excess of minute-ventilation at anaerobic threshold (β = 0.127; p=0.011) remained an independent predictor of ventilatory inefficiency. Conclusion Our data suggest that high ventilatory stimulation during exercise leading to hyperventilation is the main determinant of ventilatory inefficiency in hereditary transthyretin cardiac amyloidosis patients. This novel finding helps to better understand the mechanism of exercise intolerance in these patients where physiological limitation may be related to both heart dysfunction and abnormal pulmonary response.